"Parasitized by your own kind" : the life of the Svalbard Eider (Somateria mollissima) - Hagen, Jeanette Iren (Universitetet i Tromsø, 2008)
Conspecific brood parasitism is a subtle reproduction tactic often performed by many species. The parasitizing females lay eggs in the nest of another female of the same species, and the hosting female then incubates and raises both her own and the parasite’s offspring. Is it highly discussed why the hosting females allow this parasitism, whether she is able to detect it, or if she receives more benefits than costs by allowing it. One benefit could be that the female “dilutes” her own offspring’s chance of being caught by predators. The objects of this study were to examine some of the theories around conspecific brood parasitism in a high arctic population of Common eider (Somateria mollissima), especially if there was any correlation between body condition and parasitism, and number of neighbors laying at the same time. The results show no difference in condition between parasitized and non-parasitized females, but there is a significant relation between parasitism and number of neighbors laying eggs at the same time, and also between nest attendance and egg predation. I also found that both parasitism and egg predation seem to influence number of eggs laid by the host, indicating that the hosts are capable of both up- and down regulating their own clutch size in response to natural egg predation and parasitism.